The Effect of Adding Patchouli Essential Oil (Pogostemon Cablin Benth.) on Setting Time Of GIC - Prawira, William; Pratiwi, Deviyanti; Puspitawati, Ria; Elline, Elline; Binartha, Cipthadi Tri Oka (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Essential oils are widely incorporated into dental materials to enhance their antibacterial properties, including patchouli essential oil (PEO) derived from Pogostemon cablin Benth. PEO contains bioactive compounds such as Patchouli Alcohol (PA), phenols, steroids, and terpenoids, which contribute to its antimicrobial activity. This study aimed to evaluate the effect of PEO addition on the setting time of glass ionomer cement (GIC). Twenty cylindrical GIC specimens (2 mm × 10 mm) were tested using Vicat’s needle and divided into four groups based on the powder:PEO:liquid ratios: Group A (control), Group B (2:1:1), Group C (3:1:2), and Group D (3:2:1). Data were analysed using One-Way ANOVA and Tukey’s test (p < 0.05). The addition of PEO to GIC’s liquid is significant (p < 0,05) decreased the setting time of group B, C, and D. Modifying GIC with PEO showed a significant decrease in setting time in group B with a comparison ratio (2 : 1 : 1). All results remained within ISO 9917-1:2007 limits. Further studies are needed to assess long-term stability and mechanical performance.